Higher Platelet-to-Lymphocyte Ratio Increased the Risk of Sarcopenia in the Community-Dwelling Older Adults. Issue 1 (December 2017) - Liaw, Fang-Yih; Huang, Ching-Fu; Chen, Wei-Liang; Wu, Li-Wei; Peng, Tao-Chun; Chang, Yaw-Wen; Kao, Tung-Wei
Abstract The platelet-to-lymphocyte ratio (PLR) has been extensively studied in oncologic diseases. However, the correlation between PLR and sarcopenia remains unknown. In this cross-sectional analysis, we enrolled 3, 671 non-institutionalized individuals from the National Health and Nutrition Examination Survey (NHANES) III (1988–1994) aged ≥60 years and whose complete blood counts (CBCs), body composition measurements, and related demographic information was available. Skeletal muscle mass was assessed using a previously published equation (including age, sex, height, and bioelectrical impedance analysis). PLR values were estimated based on laboratory data. Multiple linear and logistic regression analyses, quartile-based stratified odds ratio comparisons, and trend tests were performed. Elevations in serum PLR values were significantly associated with sarcopenia status and negatively associated with skeletal muscle index. After additionally adjusting for other covariates, the significant negative correlation remained; moreover, participants with highest serum PLR values (≥155) had 2.36 times greater risk of sarcopenia than those with lowest PLR values (<90; odds ratio (OR) = 2.36; 95% confidence interval (CI): 1.21–3.31; p < 0.01). Higher PLR levels are associated with a greater risk of sarcopenia in geriatric populations. Thus, PLR as an inexpensive and easily measurable parameter can be considered as an inflammatory biomarker for sarcopenia.